An assessment of family medicine residents’ and early career physicians’ perceptions of their training: a survey from a single Canadian university - Keith Todd; Sandra Fournier; Amrita Sandhu; Sima Zahedi; Fanny Hersson-Edery; Marion Dove (Canadian Medical Education Journal, 2025)
Background: To determine if family medicine residents and recent graduates believe that the current residency program is sufficiently meeting their training needs for independent practice.